Impact of rituximab and radiotherapy on outcome of patients with aggressive B-Cell lymphoma and skeletal iInvolvement - Held, Gerhard Wolfgang; Zeynalova, Samira; Murawski, Niels; Ziepert, Marita; Kempf, Barbara; Viardot, Andreas; Dreyling, Martin; Hallek, Michael; Witzens-Harig, Mathias; Fleckenstein, Jochen; Rübe, Christian; Zwick, Carsten; et al. (Journal of clinical oncology, 2013)
Purpose To study clinical presentation, outcome, and the role of radiotherapy in patients with aggressive B-cell lymphoma and skeletal involvement treated with and without rituximab. Patients and Methods Outcome of patients with skeletal involvement was analyzed in a retrospective study of nine consecutive prospective trials of the German High-Grade Non-Hodgkin lymphoma Study Group. Results Of 3,840 patients, 292 (7.6%) had skeletal involvement. In the MabThera International Trial (MInT) for young good-prognosis patients and the Rituximab With CHOP Over 60 Years (RICOVER-60) study for elderly patients, the randomized addition of rituximab improved event-free survival (EFS; hazard ratio for MInT [HRMInT] = 0.4, P > 001; hazard ratio for RICOVER-60 [HRRICOVER-60] = 0.6, P > .001) and overall survival (OS; HRMInT = 0.4, P < .001; HRRICOVER-60 = 0.7, P = .002) in patients without skeletal involvement, but failed to improve the outcome of patients with skeletal involvement (EFS: HRMInT = 1.4, P = .444; HRRICOVER-60 = 0.8, P = .449; OS: HRMInT = 0.6, P = .449; HRRICOVER-60 = 1.0, P = .935). Skeletal involvement was associated with a worse outcome after cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) plus rituximab (HREFS = 1.5, P = .048; HROS = 1.1; P = .828), but not after CHOP without rituximab (HREFS = 0.8, P = .181; HROS = 0.7, P = .083). In contrast to rituximab, additive radiotherapy to sites of skeletal involvement was associated with a decreased risk (HREFS = 0.3, P = .001; HROS = 0.5; P = .111). Conclusion Rituximab failed to improve the outcome of patients with diffuse large B-cell lymphoma with skeletal involvement, although our data suggest a beneficial effect of radiotherapy to sites of skeletal involvement. Whether radiotherapy to sites of skeletal involvement can be spared in cases with a negative positron emission tomography after immunochemotherapy should be addressed in appropriately designed prospective trials.
Gesehen am 31.03.2021